(untitled) (Revista de Ciências Agroveterinárias, 2011)
The aims of this study was a survey of the husbandry activities used for the control of gastrointestinal helminths that are parasites on dairy cattle and diagnose the prevalence of infestation in young and adult animals in the city of Pindamonhangaba, Vale do Paraíba, São Paulo State. The survey of control practices was done througt the application of questionnaires to farmes. Most of the interviewed (52.5%) said that they treated the animals in the dry season of the year. The main reasons for the application of anthelminthic were preventive use (47.5%) and curative use (45.0%). Only 6.4% of the producers sought medical and veterinarian advice for treatment. There was a concentration of application of doses over the first 12 months of life. Producers said that they do not treat the animals in one year or more, specifically for control of worms. When he did, he sought the tick population and horn flies. The most commonly products used were ivermectins (50.0%), levamisole (37.5%) and albendazole (12.5%), with the injectable form (78.9%) being preferred to application by oral (21.1%). The weight of the animals used to calculate the dose has almost always been established by visual estimation (95.0%). The parasitological analysis of the faeces showed that 50.7% (358/706) of the animals had a positive EPG (Eggs per gram of feces) of the Order Strongylida (mean = 167.8 ± 355.5), with the incidence of parasites being higher in younger animals (mean = de 281.5 ± 461.5) when compared (p< 0.05) with adults (media de 52.3 ± 113.5). It concludes with a survey made that the management practice adopted by producers in the region (dosages during dry season, prophylactic use, without technical guidance, and pressure with ivermectin) may favour the development of resistance to anthelmintics used.